Production Performance of Broiler Chickens Supplemented with Fermented Water Hyacinth Meal in Feed - Fahmi, Katren Tika; Malesi, La; Aka, Rahim; Zulkarnain, Deki (Pascasarjana Universitas Halu Oleo, 2024)
This study aims to assess the production performance of broiler chickens supplemented with fermented water hyacinth meal in their feed and determine the optimal treatment for incorporating fermented water hyacinth meal in broiler chicken diets. The research utilized a Completely Randomized Design (CRD) with four treatments, each consisting of five replications, totaling 20 experimental units, and each replication consisting of five chickens. The treatments included: P0 = ration without the addition of fermented water hyacinth meal 0%, P1 = ration + 1.5% fermented water hyacinth meal, P2 = ration + 3% fermented water hyacinth meal, P3 = ration + 4.5% fermented water hyacinth meal. The observed parameters included feed consumption, body weight gain, and feed conversion. Based on the research results, the addition of fermented water hyacinth meal had a non-significant effect (P>0.05) on feed consumption, body weight gain, and feed conversion. It can be concluded that the addition of fermented water hyacinth meal (1.5-4.5%) has a positive impact on the production performance of broiler chickens.